The implementation of Analytical Hierarchy Process (AHP) in risk assessment and its limitation in construction in Pahang - Wei Jian, Ng (2014)
The dynamic and complex nature of the construction project caused the existence of high uncertainty and tendency for risk accident and incident to happen. Therefore, a comprehensive risk management should be implemented as a regular basic from the beginning of the project. Risk assessment can assist to identify the possible sources of risk and foreseen the possible impact of the risk to the project. It can be carried out through many tools and techniques such as Monte Carlo Simulation, Sensitivity Analysis, Critical Path Method, Fault Tree Analysis and others. Due to the nature of the industry, the duration needed in complex problem decision making process is longer. To ease the complex decision making process, Analytical Hierarchy Process (AHP) can be adopted. The technique has not been widely adopted in the Malaysia construction industry. Therefore, the objective of this study are to (1) identify the actual level of implementation of AHP in risk assessment and (2) to know the limitation when implementing AHP and not implementing AHP in risk assessment in construction industry. AHP is a Multi Criteria Decision Making (MCDM) method which illustrated in a hierarchy structure and pairwise comparison being conducted to obtain the weightage of each alternative and decision is made according to highest score. Research methodology used in this study is quantitative analysis of mean and close-ended survey questionnaire. There are some limitation to this study which included time constraints for data collection, the scope of study only covered specific area and the difficulties in accessing the data from the respondents. Research objective had been answered through the data analysis completed by using Statistical Software for Social Science (SPSS). From the analysis, the implementation of AHP in risk assessment in Pahang construction industry can be considered as low. The individual rating cannot be used as a judgment is the main limitation for AHP implementation as derived from the analysis. Meanwhile, the existence of multiple factors in the project serves as the main limitation on why AHP was not being implemented in the industry. In the future, there are still wide opportunities of this research to be continued in order to contribute in sharing the possible outcome to increase the level of implementation of AHP in the related industry. To promote the technique so that the implementation rate can be increase in the industry, intensive exposure workshop should be provided to the industry players